The Current World in the Thinking of W. W. Rostow (Czech Journal of International Relations, 2024)
W. W. Rostow, The Stages of Economic Growth, A Non-Communist Manifesto, The University Press, Cambridge 1960, 178 s.W. W. Rostow, View from the Seventh Floor, Harper & Row, New York 1964, 178 s.W. W. Rostow, The Great Transition: Tasks of the First and Second Postwar Generations, Lecture at the University of Leeds, the Department of State Bulletin, Vol. LVI, No. 1448, 1967 (27. březen), str. 491-504.